Penggunaan POE-inqury melalui blended learning terhadap hasil belajar siswa pada pembelajaran materi sistem respirasi - Triara Noerhandayani; Suhara Suhara; Rini Solihat (Assimilation: Indonesian Journal of Biology Education, 2021)
The purposes of this research were to analyze the improvement of students’ learning outcomes after participating in learning the respiratory system using POE-Inquiry through Blended Learning by Google Classroom. The research used Quasy Experiment Method. The data in this research were collected using multiple-choice questions to find out students’ level of understanding and outcome. The questionnaire supports students’ responses to the lessons. The result shows that the teaching process using POE-Inquiry through Blended Learning by Google Classroom contribute and support the progress of student learning outcome, can be seen with the result of largest of N-gain score index: first of N-gain score as much as 22,2% low category; acquisition of second N-gain score as much as 44,4% in the high category; and third N-gain score as much as 66,7% in the medium category. The result of Mann-Whitney U test on the final posttest found that the p-value (0,548) is greater than α (0.05), so it can be concluded that does not have a significant difference between Blended Learning and without Blended Learning (full face to face). Nearly all students gave positive feedback on learning the respiratory system using POE-Inquiry through Blended Learning by Google Classroom.